PENGARUH PROJECT WORK TERHADAP MOTIVASI BELAJAR MAHASISWA DALAM MATA KULIAH KAIWA II PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Novitasari, Evi Candra; Hermandra, Hermandra; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research is to study how Project Work on Kaiwa II study college students of 2018 majoring in Japanese language education, FKIP Riau University. The purpose of this research is to see the effect on group learning motivation of 2018 students on Keiwa II subject after using project work method. The object of this research is 21 college students of 2018 majoring in Japanese language education in Riau University, this research is a quasi-experiment, using non-test technique as data collection method, which is direct interview with the college students and posttest. The design of this experiment is Single-group posttest only design,which then the result will be processed using SPSS version 24 IBM for Windows. The average of students score when being interviewed is 66.984 or 67 and the average of students score when using post-test method is increased to 73. According to table Paired sample t-test, was obtained value sig(2-tailed) of 0.00<0.05, then according to the basis of decision making in paired sample t-test, it can be concluded that Ha is accepted and Ho is rejected which mean theres a significant difference between preliminary data before interview and post test. This can be seen from the increase in the average score of post-test as much as 6 points. It can be concluded project work study method influence in increasing student learning motivation to perform study in groups.Key Words: Motivation, Project Work, Kaiwa